Selling Authorization Legal Agreement Status Will Be Weighed Against Collateral Mortgage (Case Study PT. Bank Tabungan Negara (Persero) Tbk.) - Rian Dwi Anggoro; Umar Ma'ruf (Jurnal Akta, 2018)
This study aims to determine why the binding of collateral in the process of granting subsidized housing loans in PT. Bank Tabungan Negara (Persero) Tbk. Pekalongan branch office is not binding perfectly implemented using the security rights, the legal position of the agreement of power sold to the collateral to be encumbered encumbrance in the process of providing subsidized credit facilities, and a form of legal protection for authorizing the use of certificate authority to sell. This study uses empirical juridical approach or Socio Legal Research. Data collected through literature, observation and interviews. The survey results revealed that the cause of non-performance perfect binding manner using the right mortgage loan process dala subsidized home ownership in PT. Bank Tabungan Negara (Persero) Tbk. Pekalongan branch office is due to the type of housing loan subsidies are certain types of loans are regulated in the legislation which the binding process is limited to a power of attorney install security rights. On the basis of these reasons the bank asked the Notary / PPAT can issue certificates aimed at selling power if the debtor defaults, the creditor as the bank can make the sale to get the loan repayment. However, if the power of attorney install security rights has been upgraded to the Agreement of Encumbrances Encumbrance and has been registered to receive the certificate Encumbrance the collateral execution process should be subject to the laws Mortgage. Making the notarized agreement of power selling is a form of legal protection for the debtor as the authorizer.Keywords: Authorization Agreement Sell; Collateral Will Be Charged Mortgage; Credit Homeownership Subsidies.